Recurrent cutaneous basal cell carcinoma after surgical excision: A retrospective clinicopathological study. (June 2022) - Hasan, Abdulkarim; Rabie, Ahmed; Elhussiny, Mohammed; Nasr, Mohamed; Kamel, Mohamed I.; Hegab, Ahmed; El-Kady, Abdelrahman S.; Nagaty, Mahmoud E.; Seleem, Abdelhafez; Abbas, Mohammed; Elias, Abd Al-Kareem; Shemy, Gamal G.; et al.
Abstract: Background: Recurrence of basal cell carcinoma (BCC) after complete surgical excision is rarely reported. Risk factors for this negative outcome are not well-studied. We present the clinical and histological features of recurrent BCCs in our institution. Methods: All patients between January 2016 to December 2020 whose primary BCCs were excised with free surgical margins according to the histopathology report, and represented later with local recurrence were included. The medical files were retrieved to record patient's age, sex, sun exposure, tumor site, size, clinical diagnosis, histopathology variant of primary lesion, least free margin distance of the original lesion, and recurrence time. Results: Eighteen patients (11 males and 7 females ranged between 50 and 75 years old) fulfilled the inclusion criteria; all of their lesions were located in head and neck regions. The mean recurrence time was 31.2 months (11–86) and the histological variant was the same of primary in 17/18 patients. Primary tumors showed nodular subtype in 77.8% of patients and 55.6% of the primary tumors were less than 15 mm in diameter. Sun exposure history was given by 77.8% of patients while the rest of patients had non-significant exposure. All recurrent excised lesions were of free margin less than 4 mm. Conclusion: We found that the primary tumors of all studied recurrent BCCs were excised with surgical margins less than 4 mm. We recommend follow up for all excised BCCs either those of low or high risk histological variants. Tumor size does not appear a considerable risk factor for local recurrence. Highlights: We report recurrent BCCs in 18 patients, all were located in head and neck region. Sun exposure history was given by 77.8% of patients while the rest of patients gave a negative history of sun exposure. Nodular histological subtype was seen in 77.8% of patients. All primary tumors were excised by general or plastic surgeons with a surgical margin less than 4 mm.